Yaqulget Qaillun Pilartat (What the Birds Do): Yup'ik Eskimo Understanding of Geese and Those Who Study Them - Fienup-Riordan, Ann (ARCTIC, 1999)
Traditional knowledge of the effects of storm surges and changing coastal ecology on the breeding habits of geese (specifically black brant) in the coastal wetlands of southwestern Alaska was documented in a project initiated by non-Native biologists and an anthropologist. The project was both implemented and controlled by the local nonprofit regional corporation, which employed village researchers to interview elders and record their understandings of goose biology and habitat as related to storm surges. Although local and scientific understandings of brant behaviour generally agree on what is occurring (i.e., foraging habits, effects of past floods and coastal storm surges, and changes in nesting grounds), they do not always agree on why these changes are taking place. At the request of village researchers, interviews also documented Native residents' perception of geese as nonhuman persons and the non-Native view of geese as manageable wildlife, and they expressed deep resentment toward the nonlocal control that researchers and wildlife managers represent. Many feel that local control of their land and their lives is more in jeopardy than the geese. Moreover, respect for elders is as important as respect for animals in affecting management processes at the community level, creating potential conflict which younger Yup'ik men and women with training in biology find difficult to resolve. Along with articulating resistance to control, elders' testimony presents possible solutions to this contentious issue, solutions founded on personal relations between community members and scientists. Villagers' statements reflect their view that how non-Natives work in the area is as important as what is accomplished. Cooperative management of research projects like this one appears to be as important as any specific research policy or results. Un projet lancé par des biologistes allochtones et un anthropologue a permis de documenter le savoir traditionnel sur les effets des ondes de tempête et des changements dans ...